Echoes of Reaganism in Hollywood Blockbuster Movies from the 1980s to the 2010s - Ben Mna, Ilias (2021)
This book examines the reverberations of key components of Ronald Reagan’s ideology in selected Hollywood blockbuster movies. The aim of this analysis is to provide a clearer understanding of the intertwinement of cinematic spectacles with neoliberalism and neoconservatism. The analysis comprises a dissection of Reagan’s presidential rhetoric and the examination of four seminal Hollywood blockbuster movies. The time range for analysis stretches from the 1980s until the 2010s. Among the key foci are filmic content as well as production and distribution contexts. It is concluded that Reagan’s political metaphors and the corporatization of film studios in the 1970s and 1980s continue to shape much of Hollywood blockbuster filmmaking.